2013
DOI: 10.1080/10941665.2013.768283
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Factors Influencing Residents' Satisfaction with Tourism Development in Poverty-Stricken Areas: A Case Study of Five Poor Villages in China

Abstract: As one of the key stakeholders in tourism development, residents' satisfaction with tourism development (RSTD) has an important effect on the alleviation of poverty. Despite its great significance, only limited research had been conducted by researchers to explore factors influencing RSTD in poor regions. To fill the void, this study built the proposed model of RSTD in poverty-stricken areas by structural equation modeling technique. The results indicated that (1) six key influencing factors, namely, perceived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
3
12
0
3
Order By: Relevance
“…Studying residents' satisfaction is important to the success of tourism development since it enables the assessment of sustainable tourism development, the residents' perceptions toward tourism impacts, and support for tourism development [6,17,[80][81][82][83]. The literature suggests that satisfied residents perceive tourism as having positive impacts.…”
Section: Satisfaction With Local Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying residents' satisfaction is important to the success of tourism development since it enables the assessment of sustainable tourism development, the residents' perceptions toward tourism impacts, and support for tourism development [6,17,[80][81][82][83]. The literature suggests that satisfied residents perceive tourism as having positive impacts.…”
Section: Satisfaction With Local Managementmentioning
confidence: 99%
“…Several studies have found that the influence of residents' perceptions toward tourism affects their satisfaction [5,6,11,15,16]. Wang et al [17] noted that residents' satisfaction is one of the key factors leading to tourism development's success. Tourism studies show that there is a lack of research into the perceptions of residents in developing [18] and Muslim countries [19] and residents' satisfaction with tourism in the public sector [20].…”
Section: Introductionmentioning
confidence: 99%
“…Tourism development also brings positive and negative effects to individuals and families. Tourism increases residents' personal and household benefits, improves family life quality, leads to heightened self-esteem, and increases knowledge [21,[34][35][36][37]; at the same time, it also may change family composition, disturb normal life and children's education, and cause some psychological problems [38][39][40].…”
Section: Perceived Impact Of Residentsmentioning
confidence: 99%
“…Butler has divided the development and evolution of tourist destinations into six stages: exploration, involvement, development, consolidation, stagnation, decline, and rejuvenation [38]. By combining previous studies on the life cycle theory of tourist destinations [39][40][41] and the actual situation of the Lugu Lake, and by considering the start date and history of tourism development and the capacity of tourist facilities in each village, we determined the development stages of tourism in the six villages (Table 1).…”
Section: Study Areamentioning
confidence: 99%